Regional estimates of potential new production in the southern Benguela upwelling system - Waldron, Howard Neil (Department of Oceanography, 2016)
The estimation of annual potential new production at a regional scale for the decade of the 1980s provides the main focus of this thesis. New production is the proportion of total primary production which relies on the uptake of NO₃-N by the phytoplankton while potential new production assumes that all the NO₃-N available to primary producers is assimilated. The Redfield ratio between carbon and nitrogen in the marine environment was used to express rates of potential new production in terms of carbon. In order to arrive at annual estimates of potential new production it was necessary to progress from the event-scale to the annual scale. This was achieved by the adoption of two novel methods of approach. Event-scale estimates of potential new production were made by assessing the amount of NO₃-N present in the nominal euphotic zone as a result of upwelling. Remotely-sensed images of sea surface temperature (SST) coincident with or shortly after upwelling events were used in combination with a derived relationship between SST and NO₃-N concentrations integrated over the depth range of the productive surface layer in the southern Benguela region. In this way it was possible to overcome the main shortcoming of passive satellite imagery by quantifying a sub-surface variable. The event-scale estimates of potential new production were extrapolated to the annual-scale by taking into account the dynamics of the system. Sea level fluctuation at the coast preceding upwelling events was found to be related to the event-scale estimates of introduced NO₃-N and hence used as a proxy for upwelling. Using a ten year record of sea level, estimates of annual potential new production, spanning the period June to May inclusive, were made for the period 1980/81 to 1989/90. Bibliography: pages 92-108.